NILAI PENDIDIKAN PRANIKAH DALAM KITAB ‘UQUDULLUJAIN SERTA RELEVANSINYA DENGAN ISU-ISU PERNIKAHAN KONTEMPORER - Solihatunnisa, Ismi; Siti Komariah, Kokom; Budiyanti, Nurti (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2025)
This study aims to analyze the pre-marital education values in the book ‘Uqudullujain by Sheikh Muhammad bin Umar Nawawi al-Bantani al-Jawi, and its relevance to contemporary marriage issues. The research method used is qualitative with a library research approach and descriptive analysis. The primary data source is the book ‘Uqudullujain, while secondary data is obtained from related books, journals, and articles. Data collection is carried out through document analysis. The findings of this study indicate that the pre-marital education in ‘Uqudullujain provides a solid foundation for building a healthy marriage, and this understanding is relevant in addressing contemporary marriage problems, such as the phenomena of